2008
DOI: 10.1038/cgt.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral gene delivery of anti-cathepsin L single-chain variable fragment by lentiviral vector inhibits tumor progression induced by human melanoma cells

Abstract: We previously demonstrated that the switch from non-to highly tumorigenic phenotype of human melanoma cells is directly related to procathepsin L secretion, which increased cell resistance to complement-mediated cell lysis. Involvement of procathepsin L secretion in tumor growth was clearly demonstrated by three different strategies: (1) inhibition of secreted procathepsin L activity; (2) increase of procathepsin L secretion; and (3) inhibition of procathepsin L secretion. This latter strategy was triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…In this scenario, Keerthivasan et al [145] have recently shown that, at least in U87MG glioblastoma cells, vascular endothelial growth factor (VEGF) may up-regulate, at the transcriptional level, Cathepsin L. In line with these observations, Chang et al [148] have reported that, in human breast cancer cells, VEGF-A may promote angiogenesis by perturbing the cathepsin-cysteine protease inhibitor balance in venules, thus causing basement membrane degradation. Evident proof of the importance of cross-talk between Cathepsin L and VEGF in promoting tumor angiogenesis in different tumors is provided, in part, by some in vitro studies, which show that the inhibition of human procathepsin L secretion by anti-cathepsin L monoclonal antibodies results in an inhibition of tumor-induced angiogenesis in highly metastatic human melanoma cells [149,150]. In this context, Rebbaa et al [151] have recently shown that Napsul-IIe-Trp-CHO, a specific inhibitor of Cathepsin L, inhibits in vitro VEGF secretion by endothelial cells and Cathepsin L-mediated degradation of the extracellular matrix, while, in vivo, this molecule was able to inhibit tumor growth in nude mice transplanted with neuroblastoma.…”
Section: Cathepsin L and Cancer-related Bone Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…In this scenario, Keerthivasan et al [145] have recently shown that, at least in U87MG glioblastoma cells, vascular endothelial growth factor (VEGF) may up-regulate, at the transcriptional level, Cathepsin L. In line with these observations, Chang et al [148] have reported that, in human breast cancer cells, VEGF-A may promote angiogenesis by perturbing the cathepsin-cysteine protease inhibitor balance in venules, thus causing basement membrane degradation. Evident proof of the importance of cross-talk between Cathepsin L and VEGF in promoting tumor angiogenesis in different tumors is provided, in part, by some in vitro studies, which show that the inhibition of human procathepsin L secretion by anti-cathepsin L monoclonal antibodies results in an inhibition of tumor-induced angiogenesis in highly metastatic human melanoma cells [149,150]. In this context, Rebbaa et al [151] have recently shown that Napsul-IIe-Trp-CHO, a specific inhibitor of Cathepsin L, inhibits in vitro VEGF secretion by endothelial cells and Cathepsin L-mediated degradation of the extracellular matrix, while, in vivo, this molecule was able to inhibit tumor growth in nude mice transplanted with neuroblastoma.…”
Section: Cathepsin L and Cancer-related Bone Diseasesmentioning
confidence: 97%
“…Most of the Cathepsin L-targeted agents developed so far are a series of different classes of antagonist, including active site-directed low-molecular weight inhibitors many of which are endowed with a preferential selectivity for Cathepsin L [79,106,120,[153][154][155][156][157][158]. Endogenous inhibitors [159] or alternative forms of these molecules [160,161], antibodies [149,150], antisense oligonucleotides [126,139,162,163], specific ribozymes targeting Cathepsin L [90,163] or natural products [60,61] have also been proposed as potential therapeutic agents in the treatment of these diseases. Preclinical studies show that some of these molecules are effective, in vitro, in inhibiting the digestion of bone matrix proteins [60,61,67,71,79,106] at the level of resorption lacuna and in promoting bone mineralization; in vivo, these agents have been shown to suppress RANKL or M-CSF or TNF-a stimulated bone pit formation [13,67,79,120].…”
Section: Cathepsin L Inhibitors In the Treatment Of Bone Disordersmentioning
confidence: 99%
“…In hypoxic regions, activities of uPA, catB, MMP-2, MT1-MMP, MMP-9 and MMP-7 in tumor cells have been shown to be increased [139][140][141]. Immune cells, on the contrary, show a decreased activity of MMP-9 and MT1-MMP in hypoxic regions [142].…”
Section: New Therapies Involving Tumor Proteasesmentioning
confidence: 99%
“…Blockage of this secretion abolishes the tumorigenicty and metastatic potential of human melanoma cells in nude mice [12,13]. Cathepsin L in cytosol is supposed to regulate apoptosis by activation of tBid [14].…”
Section: Introductionmentioning
confidence: 99%
“…Human cathepsin L is encoded by at least five different mRNA species namely hCATL A, AI, AII, AIII and hCATL B (12)(13)(14)(15). All these hCATL mRNA species are transcribed from the same gene located on chromosome 9q 21-22 [8].…”
Section: Introductionmentioning
confidence: 99%